2016
DOI: 10.1126/scisignal.aaf2797
|View full text |Cite
|
Sign up to set email alerts
|

AML suppresses hematopoiesis by releasing exosomes that contain microRNAs targeting c-MYB

Abstract: Exosomes are paracrine regulators of the tumor microenvironment and contain complex cargo. We previously reported that exosomes released from acute myeloid leukemia (AML) cells can suppress residual hematopoietic stem and progenitor cell (HSPC) function indirectly through stromal reprogramming of niche retention factors. We found that the systemic loss of hematopoietic function is also in part a consequence of AML exosome-directed microRNA (miRNA) trafficking to HSPCs. Exosomes isolated from cultured AML or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(164 citation statements)
references
References 40 publications
(61 reference statements)
9
155
0
Order By: Relevance
“…Intriguingly, HSC in the leukemic niche enter quiescence through an unidentified process, yet appear to retain their repopulation capacity upon subsequent re-transplantation [22]. We recently showed that AML-EV, including exosomes, are highly abundant in microRNA (miR)-150 and miR-155, which both target the transcription factor c-Myb to suppress HSPC clonogenicity [17,[27][28][29]. We recently showed that AML-EV, including exosomes, are highly abundant in microRNA (miR)-150 and miR-155, which both target the transcription factor c-Myb to suppress HSPC clonogenicity [17,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, HSC in the leukemic niche enter quiescence through an unidentified process, yet appear to retain their repopulation capacity upon subsequent re-transplantation [22]. We recently showed that AML-EV, including exosomes, are highly abundant in microRNA (miR)-150 and miR-155, which both target the transcription factor c-Myb to suppress HSPC clonogenicity [17,[27][28][29]. We recently showed that AML-EV, including exosomes, are highly abundant in microRNA (miR)-150 and miR-155, which both target the transcription factor c-Myb to suppress HSPC clonogenicity [17,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Such effects have been observed both systemically and in specific tissues, including those that make up the central nervous system (16). Additionally, miR-155 can also be transferred from acute myeloid leukemia (AML) cells to healthy blood cells, resulting in the suppression of c-MYB and compromised hematopoiesis in the context of cancer (17). These examples clearly demonstrate that miRNAs contained within exosomes are involved in the communication between immune and other hematopoietic cells, during both physiological and pathological situations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AML derived Exo suppressed residual HSPC functions by “decreasing” clonogenicity and by reprogramming stroma, respectively [81,82]. Recently, BM-AML-MVs promoted the survival of healthy hematopoietic stem cells (HSCs) without changing their immature phenotype and their ability to form colonies, but inducing leukemic-like functional characteristics, such as miR21 and miR29 over-expression [83].…”
Section: Role Of Evs In the Malignancy-microenvironment Cross-talkmentioning
confidence: 99%
“…Its amount was directly correlated with white blood count cells and complex karyotypes and could be further investigated as a biomarker in AML patients. Interestingly, in an AML xenograft mouse model, Exo miR155 and other miRNAs were indicative of AML presence, thus suggesting their potential use for minimal residual disease detection [81,152]. …”
Section: Clinical Potential Of Evs As Biomarkers and Therapeuticsmentioning
confidence: 99%